Molecular Insights into Breast Cancer Treatment: An Integrated Approach of Network Pharmacology and Component Analysis for Lansium parasiticum Bark Extract - Mutiah, Roihatul; Annisa, Rahmi; Zahiro, Syayida Roisatus (Indonesian Journal of Cancer Chemoprevention, 2024)
Medicinal plants containing multi-components have the potential for multi-target genes, multi-pathways, and various effects on diverse diseases. With the increasing technological advancements, understanding the complex interactions between multi-component substances and biological systems is becoming more crucial. In this context, conventional experimental research might have limitations as it typically focuses on the impact of one component on one gene. The objective of this research is to identify compounds in the bark extract of Lansium parasiticum and elucidate the molecular mechanisms of these compounds in inhibiting the progression of breast cancer cells using a network pharmacology approach. Compound identification in Lansium parasiticum bark extract (LPBE) has been conducted using Liquid Chromatography Tandem Mass Spectrophotometry (LC-MS/MS) technique. ADMET predictions were utilized to determine the absorption and bioavailability profiles. A network pharmacology approach employing Cytoscape 3.9.1, GeneCards, Disgenet, STRING 2.0.0, SRplot, and Kyoto Encyclopedia of Genes and Genomes (KEGG) was used to predict the anti-cancer molecular mechanisms of these compounds. Seventeen active compounds have been successfully identified via LC-MS/MS. Among these, the compounds Moronic Acid, 4-Morpholineacetic Acid, and Ursolic Aldehyde were found in the highest concentrations. The results of the network pharmacology analysis indicate that the compounds in LPBE are involved in three potential pathways for breast cancer treatment: the NF-κß signaling pathway (hsa 04064), microRNA in cancer (hsa05206), and apoptosis (hsa04210). Target genes implicated in these pathways include BAX, BCL2, TNF-α, PARP1, STAT3, NOTCH1, and NF-κß1. It can be concluded that LPBE contains compounds with potential for treating breast cancer, as they are predicted to interact with relevant target pathways and genes. Therefore, further research is highly recommended, particularly in the development of drugs for breast cancer.Keywords: apoptosis, microRNA, NF-κß, TNF-α, STAT3.